A Standardized Dissection Protocol to Generate Aortic Valvular Scaffolds from Porcine Hearts - Movileanu, lonela (Acta Med Marisiensis, 2017)
OBJECTIVE: To describe a particular harvesting procedure for isolating intact porcine aortic heart valve roots as potential sources for biologic scaffolds. METHODS: Fresh porcine hearts were brought to the Tissue Engineering and Regenerative Medicine Laboratory at the University of Medicine and Pharmacy in Targu Mures. The aortic roots were extracted from the porcine hearts by anatomical dissection. For this purpose, we used a basic surgical instrument kit. This initial phase was the first step in obtaining acellular extracellular matrix as a biologic scaffold material. RESULTS: Aortic roots were isolated with preservation of the ascending aorta as well as the intact aortic sinus and coronaries together with the adjacent myocardial tissue and anterior leaflet of the mitral valve. This approach allowed for safe mounting of roots into mounting rings for perfusion decellularization. CONCLUSIONS: The described procedure is a feasible protocol for obtaining intact biological valvular scaffolds from porcine hearts. Reduced requirements regarding tools and personnel underline the easiness of aortic root harvesting using this particular procedure.